La edición digital como espacio de aprendizaje para los estudiantes de español - Clayton McCarl; Lyn Hemmingway; Stacey Lowey-Ball; Sara Menéndez; Georgina Wilson Aranguren (Journal of the Text Encoding Initiative)
This article proposes that the processes involved in digital editing create a space for collaboration and experimentation that can be useful in the context of teaching Spanish and Hispanic letters and cultures. It considers digital editing as a way to partly address the challenges that language programs are experiencing in the U.S. academy, discusses the advantages that digital editing offers students, and outlines ways to incorporate editorial projects into various teaching situations. Reflecting on their experiences at the University of North Florida, the authors seek to suggest some starting points for others who seek to explore the pedagogical possibilities of the digital transmission of Hispanic texts.